Suitability of maize crop residue fermented by Pleurotus ostreatus as feed for edible crickets: growth performance, micronutrient content, and iron bioavailability - Ventura, Martin; Holland, M. Elizabeth; Smith, Michael Bartlett; Chaparro, Jacqueline M.; Prenni, Jessica; Patz, Jonathan A.; Paskewitz, Susan; Weir, Tiffany L.; Stull, Valerie J. (Frontiers in Nutrition, 2023)
Small-scale farming of edible insects could help combat public health challenges such as protein energy malnutrition and anemia, but reliable low-cost feeds for insects are needed. In resource-limited contexts, where grains such as maize are prohibitively costly for use as insect feed, the feasibility of insect farming may depend on finding alternatives. Here, we explore the potential to modify plentiful maize crop residue with edible mushroom mycelium to generate a low-cost feed adjunct for the farmed two-spotted cricket, Gryllus bimaculatus. Mushroom farming, like insect agriculture, is versatile; it can yield nutritious food while increasing system circularity by utilizing lignocellulosic residues from row crops as inputs. Pleurotus ostreatus, is an edible basidiomycete capable of being cultivated on corn stover (Zea mays). Mushroom harvest results in abundant “spent” substrate, which we investigated as candidate feed ingredient. We created six cricket feeds containing fermented Pleurotus substrate plus an unfermented control, measuring cricket mass, mortality, and maturation weekly to evaluate cricket growth performance impacts of both fungal fermentation duration and mushroom formation. Pasteurized corn stover was inoculated with P. ostreatus mycelium and fermented for 0, 2, 3, 4, or 8 weeks. Some 4 and 8-week substrates were induced to produce mushrooms through manipulations of temperature, humidity, and light conditions. Dried fermented stover (40%) was added to a 1:1 corn/soy grain mix and fed to crickets ad libitum for 44 days. The unfermented control group showed higher survivorship compared to several fermented diets. Control group mass yield was higher than for 2 out of 6 fermented diets. Little variation in cricket iron content was observed via ICP-spectrometry across feeds, averaging 2.46 mg/100g. To determine bioavailability, we conducted in vitro Caco-2 human colon epithelial cell absorption assays, showing that iron in crickets fed fruiting-induced substrates was more bioavailable than in unfruited groups. Despite more bioavailable iron in crickets reared on post-fruiting substrates, we conclude that Pleurotus-fermented stover is an unsuitable feed ingredient for G. bimaculatus due to high mortality, variability in growth responses within treatments, and low mass yield.